Developing Web services with Java APIs for XML using WSDP - Foster, Jay A., 1965-; Wear, Natalie; Porter, Mick.; Hablutzel, Bob.; Dreamtech Software India (Rockland, Mass. : Syngress Media, 2002)
The Holy War between Microsoft Corporation and Sun Microsystems is heating up as Sun unveils JAX Pack to compete with Microsoft's .NET initiative JAX Pack is an all-in-one development kit that utilizes XML to build cross platform Web services. For companies that are developing Web services to collaborate with business partners, JAX Pack offers a faster way to develop applications while maintaining independence from any particular vendor's XML technologies. Developing Web Services with Java APIs for XML (JAX Pack) provides exhaustive coverage of Sun's recently released JAX Pack. The book assumes that readers are experienced Java developers with a solid understanding of XML. As such, the book contains five parts covering each component of JAX Pack. JAX Pack is a major product release for the most popular Web development environment First book out covering all five components of JAX Pack (JAXP, JAXR, JAXM, JAXB, and JAX-RPC) Unrivalled Web-based support with solutions@syngress.com; up-to-the minute links, white papers and analysis for one year.
Introduction to the JWSDP -- Processing XML Documents with SAX -- Processing XML Documents with DOM -- XML transformations -- Using JSTL (JSP Standard Tag Library) -- Writing SOAP clients -- Writing SOAP servers -- Using XML-based RPC -- Locating web services -- Java secure sockets layer -- Using JWSDP tools.
Includes index.
Keywords: Application software -- Development; Internet programming; Java (Computer program language).; Electronic books